ANALISIS PROMOSI EVENT BUDAYA PASOLA SEBAGAI DAYA TARIK WISATA DI KABUPATEN SUMBA BARAT - Maranisya, Ulfi; Sharen, Nawina (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2023)
This study aims to analyze the existing promotions at the Pasola cultural event in West Sumba Regency by looking at the promotion, events and tourist attractions. This research uses quantitative methods with a sample of 30 respondents. The data results using analytical tools can be concluded, namely the results of the questionnaire distributed to respondents who visited the Pasola cultural event, from the results of the validity and reliability tests in the table, showing that all statements used in the questionnaire in this study are valid and reliable from the results of the multiple linear regression equation. The conclusion in this study is that the more promotion and development of cultural events there are, the more tourist attractions issued by tourist attractions which will affect other variables such as visiting interest in West Sumba Regency.